A magnetic laponite / carboxymethyl chitosan composite adsorption material and a preparation method thereof

By preparing magnetic lithium saponite/carboxymethyl chitosan composite adsorbent materials, the problems of low mechanical strength and limited adsorption capacity of carboxymethyl chitosan were solved, achieving improved high-efficiency adsorption and regeneration performance, reducing synthesis costs, and making it suitable for water pollution treatment.

CN120695785BActive Publication Date: 2026-02-06YANBIAN UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510929653.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-07
Publication Date
2026-02-06
Estimated Expiration
2045-07-07

AI Technical Summary

Technical Problem

In existing technologies, carboxymethyl chitosan is difficult to recover after swelling in water, has low mechanical strength, and limited adsorption capacity. Traditional lithium saponite preparation is costly and has low synthesis efficiency. Magnetic adsorption materials are prone to detachment during regeneration, making it difficult to achieve efficient and low-cost adsorption and separation.

Method used

By preparing a magnetic lithium saponite/carboxymethyl chitosan composite, and using a combination of cyclic freezing and microwave irradiation techniques with a solid-phase approach, a magnetic lithium saponite/carboxymethyl chitosan composite adsorbent material was prepared, which improved its adsorption performance and regeneration capacity while reducing synthesis costs.

Benefits of technology

It achieves improved high-efficiency adsorption and regeneration performance, reduces synthesis costs, is suitable for industrial production, and shows good application prospects in water pollution control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120695785B_ABST
    Figure CN120695785B_ABST
Patent Text Reader

Abstract

The application discloses a kind of magnetic hectorite / carboxymethyl chitosan composite adsorption materials and preparation method thereof, belong to the technical field of adsorption material preparation, the preparation method is first by preparing magnetic precursor, and then preparing magnetic hectorite, and then it is compounded with carboxymethyl chitosan, finally using cyclic freezing method to prepare magnetic hectorite / carboxymethyl chitosan composite adsorption material, the obtained magnetic hectorite / carboxymethyl chitosan composite adsorption material has the characteristics such as high adsorption efficiency and good regeneration performance, while preparation is cheap, suitable for industrialized preparation, has certain use prospect in water pollution control field.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of adsorbing material preparation, and particularly relates to a magnetic nontronite / carboxymethyl chitosan composite adsorbing material and a preparation method thereof. BACKGROUND

[0002] In recent years, due to the rapid development of industrialization and the gradual improvement of people's living standards, the water pollution problem caused by heavy metal ions and organic pollutants from industrial production and domestic waste landfill has become increasingly serious and has become a global focus. The current common water treatment methods, such as chemical precipitation, ion exchange, membrane separation, etc., can achieve the removal of pollutants in water, but have problems such as high cost, low efficiency, easy to produce secondary pollution, etc. Therefore, developing efficient, environmentally friendly and reusable adsorbing materials is the research focus in the field of water pollution treatment.

[0003] Carboxymethyl chitosan (CMCS) is an important derivative of chitosan, which has good water solubility, biocompatibility and biodegradability, and is rich in active groups such as amino and carboxyl groups on the molecular chain, which can interact with various pollutants, and is an excellent natural adsorbing material. The amino and carboxyl groups of carboxymethyl chitosan can combine with heavy metal ions and organic pollutants through electrostatic interaction, coordination interaction, hydrogen bond interaction, etc., thereby realizing efficient adsorption. In addition, carboxymethyl chitosan also has the advantages of wide source, low price and environmental friendliness, and shows great application potential in the field of wastewater treatment. However, there are still some problems to be solved in using carboxymethyl chitosan alone to remove pollutants in water, such as low mechanical strength of carboxymethyl chitosan, which is difficult to recover after swelling in water and easy to cause secondary pollution of water, and the adsorption capacity of carboxymethyl chitosan is also limited, which is difficult to meet the actual adsorption demand. In order to overcome the above shortcomings, researchers try to composite it with other materials to improve its adsorption performance.

[0004] Nontronite is a kind of layered silicate material with large specific surface area and rich surface active sites, which has shown good application prospect in the adsorption field in recent years. However, the traditional nontronite preparation process generally relies on high-purity lithium salt, magnesium salt and silicate chemical raw materials, which has problems such as high cost of raw materials, complex synthesis route (usually using hydrothermal synthesis method, which has low synthesis yield due to low solid-liquid ratio in single kettle, large waste liquid discharge and low synthesis efficiency) and so on. In order to overcome these shortcomings, researchers try to develop low-cost nontronite preparation process and attempt to composite nontronite with other materials to improve its dispersibility and recyclability.

[0005] In recent years, by introducing magnetic nanoparticles into adsorbent materials, magnetic adsorbent materials are prepared to improve the separation and recovery ability of adsorbent materials, so as to realize high utilization of materials and reduce treatment cost, which has attracted wide attention in the field of adsorbent materials. However, the self-aggregation of magnetic materials and the random distribution of functional groups (or defects) on the surface of adsorbent materials make it difficult to ensure uniform and efficient loading of magnetic materials. In addition, due to the weak interaction between magnetic materials and adsorbent materials, the magnetic materials are easy to separate during the regeneration and recycling process of adsorbent materials, which seriously reduces the regeneration performance of magnetic adsorbent materials. How to avoid complex magnetization material synthesis steps and cumbersome magnetic modification process, low-cost, simple realization of uniform distribution of magnetic materials on adsorbent medium, and at the same time, strong interface interaction between them, is the key to the preparation of adsorbent materials with high adsorption performance, high separation and regeneration performance at low cost. SUMMARY

[0006] In view of the problems in the prior art in preparing magnetic hectorite composite adsorbent materials, the present application provides a magnetic hectorite / carboxymethyl chitosan composite adsorbent material and a preparation method thereof. The preparation method first prepares a magnetic precursor, then prepares a magnetic hectorite, and then composites the magnetic hectorite with carboxymethyl chitosan. Finally, a magnetic hectorite / carboxymethyl chitosan composite adsorbent material is prepared by a cyclic freezing method. The obtained magnetic hectorite / carboxymethyl chitosan composite adsorbent material has the characteristics of high adsorption efficiency and good regeneration performance, and the preparation cost is low, which is suitable for industrialized preparation and has certain application prospect in the field of water pollution control.

[0007] The present application is realized by the following technical solutions:

[0008] A preparation method of a magnetic hectorite / carboxymethyl chitosan composite adsorbent material, specifically comprising the following steps:

[0009] S1: Carboxymethyl chitosan is added to ultrapure water, and dissolved under the condition of temperature 60-70℃ and magnetic stirring to form a carboxymethyl chitosan gel;

[0010] S2: Magnetic hectorite is added to the carboxymethyl chitosan gel obtained in step S1, and the magnetic stirring is continued until complete dissolution to obtain a mixture A;

[0011] S3: The mixture A is frozen at-80℃ for 12h, then taken out and thawed at 25℃ for 12h, and the freezing-thawing process is repeated for 3-5 times. The treated product is freeze-dried at-80℃ for 24-72 hours to obtain a magnetic hectorite / carboxymethyl chitosan composite adsorbent material;

[0012] Wherein, the magnetic stirring is carried out by using a magnetic heating stirrer with a magnetic stirrer.

[0013] Further, in step S1, the carboxymethyl chitosan is added in the ultrapure water in an amount of 20-35 g / L.

[0014] In step S3, the mass ratio of the magnetic hectorite to the carboxymethyl chitosan is 0.5-1:1.

[0015] Further, in step S2, the magnetic hectorite is prepared by the following method, specifically comprising the following steps:

[0016] A1. A lithium source, a magnesium source and a magnetic precursor are mixed in a molar ratio of 1.0:3.0:1.7-3.0 and stirred thoroughly, and the obtained mixture is denoted as mixture I;

[0017] A2. The mixture I is transferred to a polytetrafluoroethylene hydrothermal reactor inner liner tank, and 3-5 ml of an ammonia solution is added to the bottom of the polytetrafluoroethylene hydrothermal reactor inner liner tank.

[0018] A3. The polytetrafluoroethylene hydrothermal reactor inner liner tank is loaded into a stainless steel reactor, and placed in a constant temperature oven for reaction at a temperature of 110-200 ℃ for 24-72 h.

[0019] A4. After the reaction is completed, the polytetrafluoroethylene hydrothermal reactor inner liner tank is taken out, the solid product is centrifuged and washed to neutral, the solid product is transferred with deionized water, and the obtained material is freeze-dried, and the obtained solid powder is the magnetic hectorite.

[0020] Further, in step A1, the lithium source is one or a mixture of two of lithium fluoride, lithium carbonate and lithium hydroxide monohydrate; and the magnesium source is one or a mixture of two of magnesium chloride, magnesium carbonate and magnesium hydroxide.

[0021] In step A2, the ammonia water used is a laboratory labeled 25% concentrated ammonia water; the mixture I and the ammonia solution are separated by a polytetrafluoroethylene net, that is, only the ammonia water is heated to form an alkaline vapor as a reaction medium during the reaction.

[0022] In step A4, the freeze-drying conditions are: freeze temperature of-80 ℃, and freeze-drying time of 1-3 days.

[0023] Further, in step A1, the magnetic precursor is prepared by the following method, specifically comprising:

[0024] B1. Clay-based polymers and magnetic substances are mixed uniformly in a mass ratio of 1:0.05-1, and the obtained mixture is denoted as mixture II;

[0025] B2. The mixture II is transferred to a polytetrafluoroethylene hydrothermal reactor inner liner tank, and 3-5 ml of an ammonia solution is added to the bottom of the polytetrafluoroethylene hydrothermal reactor inner liner tank.

[0026] B3. Put the polytetrafluoroethylene hydrothermal reactor liner tank in the stainless steel reactor, and place it in the constant temperature oven, and react at a temperature of 150-170℃ for 3-6h;

[0027] B4. After the reaction is completed, take out the polytetrafluoroethylene hydrothermal reactor liner tank, and take out the solid product in the reactor liner tank. The obtained mixture is denoted as mixture III;

[0028] B5. Put the mixture III obtained in step B4 into a microwave digestion tank, and add 3-5ml of ammonia solution at the bottom of the microwave digestion tank;

[0029] B6. Put the loaded microwave digestion tank into the microwave digestion instrument, and irradiate it at a certain temperature under specific irradiation conditions. The irradiation conditions are: irradiation temperature of 120-150℃, and irradiation cycle of 3-8;

[0030] B7. After the reaction is completed, take out the microwave irradiated microwave digestion tank, and filter the solid product to neutral, and place it in a vacuum oven at 90℃ for 12h. The vacuum degree of the vacuum oven is 0.07MPa. The obtained solid powder is the magnetic precursor.

[0031] Further, in step B1, the magnetic substance is one or a combination of Fe2O3, Fe3O4, FeCl2, Co3O4, CoCl2, and NiCl2;

[0032] In step B2, the ammonia water used is an ammonia water solution obtained by mixing 25% concentrated ammonia water and deionized water in a volume ratio of 1:1; the mixture II and the ammonia water solution are separated by a polytetrafluoroethylene net, i.e. the reaction in step B3 only relies on the alkaline steam formed by heating the ammonia water solution as the reaction medium;

[0033] In step B5, the ammonia water used is a 25% concentrated ammonia water labeled in the laboratory; the mixture III and the ammonia water solution are separated by a polytetrafluoroethylene net, i.e. the reaction in step B6 only relies on the alkaline steam formed by heating the ammonia water as the reaction medium.

[0034] Further, in step B6, the irradiation cycle is specifically 100w irradiation for 10s, 150w irradiation for 10s, 200w irradiation for 10s, 250w irradiation for 10s, 300w irradiation for 10s, and stop for 10s.

[0035] Further, in step B1, the clay-based mineral polymer is prepared by the following method, specifically including:

[0036] C1, select natural clay raw ore flotation after impurity removal, grinding to powder, screening through 80 mesh screen, obtaining natural clay powder;

[0037] C2, the natural clay powder and acid liquid are loaded into a microwave digestion tank according to a certain solid-liquid ratio, and the mass-volume ratio of the natural clay and the acid liquid is 1:2.5-5 g / ml;

[0038] C3, the microwave digestion tank loaded in step C2 is loaded into a microwave digestion instrument, and irradiated at a certain temperature according to specific irradiation conditions, specifically, the irradiation temperature is 150-200 ℃, and the irradiation cycle is 30-60;

[0039] C4, the microwave digestion tank after microwave irradiation is taken out, the solid product is suction filtered to neutral, and placed in a constant temperature oven at 80-90 ℃ for drying for 12 h, and the obtained solid powder is the clay base polymer.

[0040] Further, in step C1, the natural clay is one or more of kaolin, montmorillonite, rectorite, illite and halloysite;

[0041] In step C2, the acid liquid is hydrochloric acid with a concentration of 2-4 mol / L;

[0042] In step C2, the natural clay and the acid liquid are separated by a polytetrafluoroethylene net, that is, only the acid liquid is heated to form acidic steam as the reaction medium during microwave irradiation;

[0043] In step C3, the irradiation cycle is specifically 200w irradiation for 10s, 230w irradiation for 10s, 270w irradiation for 10s, 330w irradiation for 10s, 350w irradiation for 10s, and stopping for 10s.

[0044] Compared with the prior art, the advantages of the present application are as follows:

[0045] 1. Significantly improve the adsorption performance and regeneration capacity, because the magnetic hectorite not only provides a certain adsorption capacity, but also acts as a spatial crosslinking point of carboxymethyl chitosan, so that the composite material has a more complex spatial network, which not only increases the specific surface area of the material, but also provides more adsorption active sites. In addition, the addition of magnetic hectorite also endows the material with higher regeneration capacity, which also makes the material more advantageous in the adsorption field.

[0046] 2. Reduce the synthesis cost and environmental pollution, in the preparation process of magnetic hectorite, the clay base polymer produced by acidolysis of natural clay is used as the synthesis raw material, which to some extent reduces the pollution problem of the synthesis raw material caused by the use of silicon-containing chemicals (such as silica gel), and also reduces the synthesis cost of lithium soapstone, which is convenient for industrial actual production;

[0047] 3. In the process of obtaining geomineral polymer, the superimposed composite process of solid phase method and microwave progressive irradiation method is adopted, so that on the one hand, low concentration of acid liquid can play the effect of high concentration of acid liquid, effectively improving the use efficiency of acid liquid, and at the same time, through the addition of a small amount of acid liquid, the acid liquid can be recycled for multiple times. On the other hand, the natural clay powder is directly irradiated by microwave, and because different chemical bonds have differences in receiving microwave, the natural clay powder can be directly activated, and the activated and broken chemical bonds have consistency. The broken chemical bonds can be better combined with the magnetic particles through chemical interaction.

[0048] 4. In the process of preparing magnetic precursor, the solid phase preparation method and microwave progressive irradiation method are adopted to weaken the influence of synthesis process on the magnetism of magnetic particles to the greatest extent, and the microwave irradiation technology is used to quickly identify the chemical loading behavior between the magnetic particles and the geomineral polymer.

[0049] 5. In the process of preparing magnetic hectorite, the solid phase preparation method is combined with freeze-drying process, which not only eliminates the inconvenience of hydrothermal synthesis of hectorite, but also reduces the loss of magnetic particles. BRIEF DESCRIPTION OF DRAWINGS

[0050] In order to more clearly illustrate the specific embodiments of the present application or the technical solutions in the prior art, the drawings needed in the description of the specific embodiments or the prior art will be briefly introduced below. In all the drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, each element or part is not necessarily drawn according to the actual proportion.

[0051] Figure 1 XRD pattern of clay geomineral polymer in implementation case 1;

[0052] Figure 2 XRD pattern of magnetic precursor in implementation case 1;

[0053] Figure 3 XRD pattern of magnetic hectorite in implementation case 1;

[0054] Figure 4 Actual picture of the prepared material after water absorption in implementation case 1. DETAILED DESCRIPTION

[0055] In order to clearly and completely describe the technical solutions of the present application and the specific working process thereof, in combination with the drawings of the specification, the specific embodiments of the present application are as follows:

[0056] Example 1

[0057] The embodiment provides a preparation method of a magnetic nontronite / carboxymethyl chitosan composite adsorption material, and has the characteristics that the method comprises the following steps:

[0058] S1: carboxymethyl chitosan is weighed and added into ultrapure water, the solution is stirred on a magnetic heating stirrer at a temperature of 60 DEG C by using a magnetic stirrer until the carboxymethyl chitosan is completely dissolved in the ultrapure water, and a carboxymethyl chitosan gel is obtained;

[0059] S2: magnetic nontronite is added into the carboxymethyl chitosan gel, and stirring is performed on the magnetic heating stirrer by using a magnetic stirrer until the magnetic nontronite is completely dissolved, and the obtained substance is mixture A;

[0060] S3: the mixture A is frozen at an environment of-80 DEG C for 12h, and then taken out and kept still at an environment of 25 DEG C for 12h, and the above process is repeated for three times; the obtained product is freeze-dried, and the obtained product after complete drying is a magnetic nontronite / carboxymethyl chitosan composite adsorption material; the temperature of freeze-drying is-80 DEG C, and the freezing time is 24h.

[0061] In the embodiment, in step S1, the addition amount of carboxymethyl chitosan in the ultrapure water is 20g / L.

[0062] In step S2, the mass ratio of the used magnetic nontronite to carboxymethyl chitosan is 1:1.

[0063] In the embodiment, the magnetic nontronite in step S2 is prepared by the following steps:

[0064] A1. lithium source, magnesium source and magnetic precursor are mixed according to a molar ratio of 1.0:3.0:3.0, and the obtained mixture is recorded as mixture I;

[0065] A2. the mixture I is transferred into a 100ml polytetrafluoroethylene hydrothermal reactor inner liner tank, 5ml ammonia solution is added into the bottom of the polytetrafluoroethylene hydrothermal reactor inner liner tank;

[0066] A3. the polytetrafluoroethylene hydrothermal reactor inner liner tank in step A2 is loaded into a stainless steel reactor, and is placed in a constant temperature oven, and the temperature is 200 DEG C, and the reaction is carried out for 24h;

[0067] A4. after the reaction is completed, the polytetrafluoroethylene hydrothermal reactor inner liner tank is taken out, the solid product is centrifuged and washed to neutral, the solid product is transferred with deionized water, the solid product is transferred, and the obtained substance is freeze-dried, and the obtained solid powder is magnetic nontronite.

[0068] In the embodiment, in step A1, the lithium source is lithium fluoride, and the magnesium source is magnesium chloride.

[0069] In the present embodiment, in step A2, the ammonia water used is ammonia water with a concentration of 25% as indicated by the laboratory; the mixture I and the ammonia water solution are separated by a polytetrafluoroethylene net, that is, only the ammonia water is heated to form an alkaline vapor as the reaction medium during the reaction.

[0070] In the present embodiment, in step A4, the freeze-drying conditions are: freezing temperature -80℃, and freeze-drying time 3 days.

[0071] In the present embodiment, in step A1, the magnetic precursor is prepared by the following method, specifically comprising:

[0072] B1. The clay-based mineral polymer and the magnetic substance are mixed uniformly at a mass ratio of 1:0.05, and the obtained mixture is recorded as mixture II;

[0073] B2. The mixture II is transferred to a 100 ml polytetrafluoroethylene hydrothermal reactor inner liner, and 3 ml of ammonia water solution is added to the bottom of the polytetrafluoroethylene hydrothermal reactor inner liner;

[0074] B3. The polytetrafluoroethylene hydrothermal reactor inner liner prepared in step B2 is loaded into a stainless steel reactor, which is placed in a constant temperature oven, and the reaction is carried out at a temperature of 170℃ for 3h;

[0075] B4. After the reaction is completed, the polytetrafluoroethylene hydrothermal reactor inner liner is taken out, and the solid product in the reactor inner liner is taken out, and the obtained mixture is recorded as mixture III;

[0076] B5. The mixture III obtained in step B4 is loaded into a microwave digestion tank, and 3 ml of ammonia water solution is added to the bottom of the microwave digestion tank;

[0077] B6. The loaded microwave digestion tank is loaded into a microwave digestion instrument, and irradiated at a certain temperature under specific irradiation conditions, specifically at an irradiation temperature of 120℃, and the irradiation cycle is 8;

[0078] B7. After the reaction is completed, the microwave digestion tank after microwave irradiation is taken out, the solid product is suction filtered to neutral, and placed in a vacuum oven at 90℃ for 12h (vacuum degree 0.07MPa), and the obtained solid powder is the magnetic precursor.

[0079] In the present embodiment, in step B2, the ammonia water used is ammonia water solution obtained by uniformly mixing 25% ammonia water as indicated by the laboratory with deionized water at a volume ratio of 1:1; the mixture II and the ammonia water solution are separated by a polytetrafluoroethylene net, that is, only the ammonia water solution is heated to form an alkaline vapor as the reaction medium during the reaction of step B3.

[0080] In the present embodiment, in step B5, the ammonia water used is a 25% ammonia water of a laboratory indicated concentration; the mixture III and the ammonia water solution are separated by a polytetrafluoroethylene net, that is, the reaction in step B6 only relies on the ammonia water heated to form an alkaline vapor as the reaction medium.

[0081] In the present embodiment, in step B6, the irradiation cycle mentioned is specifically 100w irradiation for 10s, 150w irradiation for 10s, 200w irradiation for 10s, 250w irradiation for 10s, 300w irradiation for 10s, and stopping for 10s.

[0082] In the present embodiment, in step B1, the magnetic substance is Fe3O4.

[0083] In the present embodiment, in step B1, the clay-based mineral polymer is prepared by the following method, specifically comprising:

[0084] C1, after the natural clay raw ore is impurity-removed by flotation, it is ground into powder and sieved through an 80-mesh sieve to obtain a natural clay powder;

[0085] C2, the natural clay powder and an acid solution are loaded into a microwave digestion tank according to a certain solid-liquid ratio, and the ratio range is natural clay: acid solution = 1:2.5 g / ml;

[0086] C3, the microwave digestion tank loaded in step C2 is loaded into a microwave digestion instrument, and irradiated at a certain temperature according to specific irradiation conditions, specifically, the irradiation temperature is 200℃, and the irradiation cycle is 30;

[0087] C4, the microwave digestion tank after microwave irradiation is taken out, the solid product is suction-filtered to neutral, and placed in a constant temperature oven at 80℃ for drying for 12h, and the obtained solid powder is the clay-based mineral polymer.

[0088] In the present embodiment, in step C1, the natural clay is kaolin;

[0089] In step C2, the acid solution is hydrochloric acid, and the concentration is 2 mol / L;

[0090] In step C2, the natural clay and the acid solution are separated by a polytetrafluoroethylene net, that is, only the acid solution is heated to form an acidic vapor as the reaction medium during the microwave irradiation process;

[0091] In step C3, the irradiation cycle is specifically 200w irradiation for 10s, 230w irradiation for 10s, 270w irradiation for 10s, 330w irradiation for 10s, 350w irradiation for 10s, and stopping for 10s.

[0092] Example 2 is the same as Example 1 except that the temperature used in the process of obtaining the carboxymethyl chitosan gel in step S1 is 70℃; in step S3, the mixture A is frozen in an environment of -80℃ for 12h, then taken out and left in an environment of 25℃ for 12h, and the above process is repeated 5 times. In the step A1 of preparing the magnetic hectorite, the lithium source, the magnesium source, and the magnetic precursor are in a molar ratio of 1.0:3.0:3.0, wherein the lithium source is selected from lithium carbonate; the magnesium source is magnesium hydroxide; in the step A2 of preparing the magnetic hectorite, 5ml of ammonia solution is added to the bottom of the polytetrafluoroethylene hydrothermal reaction inner liner kettle; in the step A3 of preparing the magnetic hectorite, the reaction temperature used is 110℃, and the reaction time is 72h; in the step A4 of preparing the magnetic hectorite, the freeze-drying temperature is -80℃, and the freeze-drying time is 72h.

[0093] Example 3 is the same as Example 1 except that in the step B1 of preparing the magnetic precursor, the clay-based polymer and the magnetic substance are in a mass ratio of 1:0.5; in the step B2, 5ml of ammonia solution is added to the bottom of the polytetrafluoroethylene hydrothermal reaction kettle inner liner; in the step B3, the reaction temperature is 150℃, and the reaction time is 6h; in the step B5, 5ml of ammonia solution is added to the bottom of the polytetrafluoroethylene hydrothermal reaction kettle inner liner; in the step B6, the irradiation temperature is 150℃, and the irradiation cycle is 3;

[0094] Example 4 is the same as Example 1 except that the magnetic substance FeCl2 is used;

[0095] Example 5 is the same as Example 1 except that in the step C2, the natural clay: acid solution = 1:2.5 g / ml; in the step C3, the irradiation temperature is 150℃, and the irradiation cycle is 60; in the step C4, the solid product is filtered to neutral and placed in an oven at 90℃ for 12h; in the step C2, the acid solution used is hydrochloric acid, and the concentration thereof is 4 mol / L.

[0096] Example 6 is the same as Example 1 except that the natural clay used in the step C1 is halloysite.

[0097] Example 7 is the same as Example 1 except that the natural clay used in the step C1 is illite.

[0098] Example 8 is the same as Example 1 except that the amount of carboxymethyl chitosan added in the step S1 is 35g / L; in the step S2, the mass ratio of the magnetic hectorite and the carboxymethyl chitosan used is 0.5:1.

[0099] From Figure 1As can be seen from the figure, the clay-based polymer shows an amorphous structure, indicating that its inherent crystal structure has been completely depolymerized and is in an amorphous state.

[0100] As can be seen from the figure, the magnetic particles have been determined to be compounded with the clay-based polymer according to the diffraction peaks. Figure 2

[0101] As can be seen from the figure, the magnetic lithium mica used is determined according to the diffraction peaks. Figure 3

[0102] Figure 4 The physical picture of the prepared composite material.

[0103] Experimental data

[0104] Table 1 is the test results of the first adsorption performance and the adsorption performance after 9 times of regeneration of the magnetic lithium mica of the implementation cases 1-8

[0105] Number Adsorption efficiency (first time) Adsorption efficiency (tenth time) Example 1 99% 94% Example 2 99% 93% Example 3 99% 94% Example 4 99% 92% Example 5 99% 94% Example 6 99% 94% Example 7 99% 91% Example 8 99% 93%

[0106] Adsorption experiment

[0107] A certain mass of magnetic lithium mica / carboxymethyl chitosan composite adsorption material (0.2 g) was weighed into a conical flask, a certain volume of lead-containing heavy metal ion wastewater (100 mL) was added, and the conical flask was oscillated at 30°C for 2h. After adsorption, the supernatant was taken and centrifuged at a speed of 8000r / min for 15min. The concentration of heavy metal ions in the wastewater before and after adsorption was determined by X-ray diffraction (the initial concentration C0was 1000.0mg·L¹, and the concentration of heavy metal ions in the solution after adsorption was C t The removal rate of heavy metal ions (R, %) was calculated according to the following formula.

[0108]

[0109] The adsorbed adsorption material was collected under the action of an external magnetic field, and then a regeneration adsorption experiment was performed. Before each regeneration adsorption, it needs to be ultrasonically treated at room temperature (20-30°C) (the ultrasonic frequency used is 40KHz, and the ultrasonic time is 15min). After ultrasonic treatment, the adsorption experiment was performed.

[0110] As can be seen from Table 1, the magnetic lithium mica / carboxymethyl chitosan composite adsorption material prepared by the implementation cases 1-8 has excellent adsorption performance for lead-containing heavy metal ion wastewater.

[0111] ​​The preferred embodiments of the present application are described in detail above with reference to the drawings, but the present application is not limited to the specific details of the above-described embodiments, and various simple modifications can be made to the technical solutions of the present application within the technical concept of the present application, and these simple modifications all belong to the protection scope of the present application.

[0112] In addition, it should be noted that each specific technical feature described in the above specific embodiments can be combined in any appropriate manner without contradiction, and in order to avoid unnecessary repetition, various possible combinations are not described again by the present application.

[0113] In addition, various different embodiments of the present application can also be combined in any manner, as long as it does not deviate from the idea of the present application, and it should also be considered as disclosed by the present application.

Claims

1. A method for preparing a magnetic lithium saponite / carboxymethyl chitosan composite adsorbent material, characterized in that, Specifically, the steps include the following: S1: Add carboxymethyl chitosan to ultrapure water and dissolve it under a temperature of 60-70℃ and magnetic stirring to form carboxymethyl chitosan gel. S2: Add magnetic lithium soapstone to the carboxymethyl chitosan gel obtained in step S1, and continue to stir magnetically until completely dissolved to obtain mixture A; S3: Freeze mixture A at -80℃ for 12 hours, then thaw it at 25℃ for 12 hours. Repeat the above freeze-thaw process 3-5 times. Freeze-dry the treated product at -80℃ for 24-72 hours to obtain magnetic lithium saponite / carboxymethyl chitosan composite adsorbent material. Among them, magnetic stirring is carried out using a magnetic heating stirrer in conjunction with a magnetic stir bar; In step S2, the magnetic lithium saponite is prepared by the following method, specifically including the following steps: A1. Mix the lithium source, magnesium source and magnetic precursor in a molar ratio of 1.0:3.0:1.7-3.0 and stir thoroughly. The resulting mixture is denoted as Mixture I. A2. Transfer the above mixture I to a polytetrafluoroethylene hydrothermal reactor lined tank, and add 3-5 ml of ammonia solution to the bottom of the polytetrafluoroethylene hydrothermal reactor lined tank; A3. Place the prepared polytetrafluoroethylene hydrothermal reactor liner into the stainless steel reactor, and put it in a constant temperature oven to react for 24-72 hours at a temperature of 110-200℃. A4. After the reaction is complete, remove the inner liner of the polytetrafluoroethylene hydrothermal reactor, centrifuge and wash the solid product until it is neutral, transfer the solid product with deionized water, and freeze-dry the obtained substance. The resulting solid powder is magnetic lithium soapstone. In step A1, the magnetic precursor is prepared by the following method, specifically including: B1. Mix the clay base mineral polymer and the magnetic material at a mass ratio of 1:0.05-1 until homogeneous. The resulting mixture is referred to as Mixture II. B2. Transfer the above mixture II to the inner liner of the polytetrafluoroethylene hydrothermal reactor, and add 3-5 ml of ammonia solution to the bottom of the inner liner of the polytetrafluoroethylene hydrothermal reactor; B3. Place the polytetrafluoroethylene hydrothermal reactor liner prepared in step B2 into a stainless steel reactor, and place it in a constant temperature oven to react for 3-6 hours at a temperature of 150-170℃. B4. After the reaction is complete, remove the inner liner of the polytetrafluoroethylene hydrothermal reactor and take out the solid product from the inner liner of the reactor. The resulting mixture is called mixture III. B5. Place the mixture III obtained in step B4 into a microwave digestion vessel, and add 3-5 ml of ammonia solution to the bottom of the microwave digestion vessel; B6. Place the assembled microwave digestion vessel into a microwave digester and irradiate it at a certain temperature under specific irradiation conditions. The irradiation conditions are: irradiation temperature 120-150℃, irradiation cycle 3-8. B7. After the reaction is complete, remove the microwave digestion vessel after microwave irradiation, filter the solid product until it is neutral, and place it in a vacuum oven at 90°C for 12 hours. The vacuum degree of the vacuum oven is 0.07 MPa. The resulting solid powder is the magnetic precursor.

2. The preparation method of the magnetic lithium saponite / carboxymethyl chitosan composite adsorbent material as described in claim 1, characterized in that, In step S1, the amount of carboxymethyl chitosan added to the ultrapure water is 20-35 g / L; In step S3, the mass ratio of magnetic lithium saponite to carboxymethyl chitosan is 0.5-1:

1.

3. The preparation method of the magnetic lithium saponite / carboxymethyl chitosan composite adsorbent material as described in claim 1, characterized in that, In step A1, the lithium source is one or a mixture of two of lithium fluoride, lithium carbonate, and lithium hydroxide monohydrate; the magnesium source is one or a mixture of two of magnesium chloride, magnesium carbonate, and magnesium hydroxide. In step A2, the ammonia solution has a laboratory-labeled concentration of 25%; mixture I and the ammonia solution are isolated by a polytetrafluoroethylene mesh, meaning that during the reaction, only the alkaline vapor formed by heating the ammonia solution serves as the reaction medium. In step A4, the freeze-drying conditions are: freezing temperature -80℃, freeze-drying time 1-3 days.

4. The preparation method of the magnetic lithium saponite / carboxymethyl chitosan composite adsorbent material as described in claim 1, characterized in that, In step B1, the magnetic material is one or a combination of more of Fe2O3, Fe3O4, and Co3O4; In step B2, the ammonia solution is obtained by mixing concentrated ammonia solution with a laboratory-labeled concentration of 25% with deionized water at a volume ratio of 1:

1. The mixture II and the ammonia solution are isolated by a polytetrafluoroethylene mesh, meaning that the reaction in step B3 relies solely on the alkaline vapor formed by heating the ammonia solution as the reaction medium. In step B5, the ammonia solution has a laboratory-labeled concentration of 25%; the mixture III and the ammonia solution are isolated by a polytetrafluoroethylene mesh, meaning that the reaction in step B6 relies solely on the alkaline vapor formed by heating the ammonia solution as the reaction medium.

5. The preparation method of the magnetic lithium saponite / carboxymethyl chitosan composite adsorbent material as described in claim 1, characterized in that, In step B6, the irradiation cycle specifically consists of 100W irradiation for 10s, 150W irradiation for 10s, 200W irradiation for 10s, 250W irradiation for 10s, 300W irradiation for 10s, followed by a 10s pause.

6. The preparation method of the magnetic lithium saponite / carboxymethyl chitosan composite adsorbent material as described in claim 1, characterized in that, In step B1, the clay-based mineral polymer is prepared by the following method, specifically including: C1. After selecting natural clay ore and removing impurities by flotation, grind it into powder and sieve it through an 80-mesh sieve to obtain natural clay powder. C2. Natural clay powder and acid solution are placed into a microwave digestion vessel in a certain solid-liquid ratio. The mass-volume ratio of natural clay to acid solution is 1:2.5-5 g / ml. C3. Place the microwave digestion vessel prepared in step C2 into a microwave digester and irradiate it at a certain temperature under specific irradiation conditions, specifically an irradiation temperature of 150-200 ℃ and an irradiation cycle of 30-60 cycles. C4. Remove the microwave digestion vessel after microwave irradiation, filter the solid product until it is neutral, and place it in a constant temperature oven at 80-90℃ for 12 hours to dry. The resulting solid powder is the clay base mineral polymer.

7. The preparation method of the magnetic lithium saponite / carboxymethyl chitosan composite adsorbent material as described in claim 6, characterized in that, In step C1, the natural clay is one or more of kaolin, montmorillonite, rettoite, illite, and halloysite; In step C2, the acid solution is hydrochloric acid with a concentration of 2-4 mol / L; In step C2, the natural clay and the acid solution are isolated by a polytetrafluoroethylene mesh, meaning that during microwave irradiation, the acid solution is heated to form acidic vapor as the reaction medium. In step C3, the irradiation cycle specifically consists of 200W irradiation for 10s, 230W irradiation for 10s, 270W irradiation for 10s, 330W irradiation for 10s, 350W irradiation for 10s, followed by a 10s pause.

8. A magnetic lithium saponite / carboxymethyl chitosan composite adsorbent material, characterized in that, Prepared by the method described in any one of claims 1-7.

Citation Information

Patent Citations

  • Preparation method and application of magnetic hectorite composite polymer dye adsorbent for treating dye wastewater

    CN113893832A

  • Self-gelation chitosan / hectorite composite sponge as well as preparation method and application thereof

    CN116731387A

  • Method for preparing nano hectorite by using clay as raw material through microwave irradiation

    CN118324153A